PELATIHAN âCREATIVE PARENTING TODAYâ CARA PRAKTIS MEMICU DAN MAMACU KREATIVITAS DAN PRIBADI ANAK MELALUI POLA ASUH KREATIF BAGI ORANG TUA DI CABENGE KABUPATEN SOPPENG - A., Anriani; R., Riska; I., Irmayanti (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Parenting style is one of the significant factor that helped to profile the children. This is based on assumption that education in the family is the first and primary education obtained by children, which is cannot be replaced by any other institution. For instance children superkids models they were displaced from their childhood, and as adults they will be adults but still childish. So parenting parents largely determines the attitude and the nature of his future. To that end we strive to provide training to parents in the district Cabbenge Soppeng to be "Creative Parenting Today". Through this training at least appear to be able to change the consciousness of parenting that has been less appropriate. The goals of the training are parents in kindergarten Al - Khair Cabenge, with the hope they become parents who are able to parenting a next brilliant generation. The method used in this training is observation, preparation, training, evaluation, and preparation of reports. The results achieved for the distributed questionnaire was 80 percent. The results of questionnaires filled out by 20 participants, suggests that this training event was success.